Aerodynamic airfoil at critical angles of attack - Kostić, Čedomir Lj.; Rašuo, Boško P. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Aircraft construction experts must not neglect the behavior of aircraft in extreme or closely extreme flight conditions, such as flights at critical angles of attack, where a normal flight can be easily converted into a stall. This paper highlights the essential factors that influence the behavior of aircraft in flight at critical angles of attack. Based on the available experimental results and estimations, the performances of airfoils were analysed depending on air flow conditions (categorized according to Mach and Reynolds numbers), airfoil shapes, dynamics of the transition of angles of attack, description of the flow around airfoils with increasing the angle of attack upon reaching a critical value, and the effect of roughness of airfoil surfaces at critical angles of attack. The paper gives a physical interpretation of a lift decrease and a stall. It minutely describes the origin of flow separation and categorizes airfoil sections by type of separation and their behavior during the flow at the critical angle of attack. Based on modern aerodynamics, this paper aims to show and explain the issues and the most important characteristics of the flow past the body at critical angles of attack and give practical recommendations for airfoil design. As such, it may be of interest to pilots and engineers as well as to educational and research institutions.